Benchmarking avi-tourism literacy rates among Gauteng school learners - D. H. Tustin; N. Conradie (South African Journal of Business Management, 2016)
Literacy on birds and the natural environment among young citizens is critical in addressing current and emerging environmental challenges. To improve the future awareness, involvement, knowledge, values and pro-environmental behaviour of young South Africans towards birds, the natural habitat of birds and avi-tourism, this article benchmarks avi-tourism literacy rates among secondary school learners. The study arrived at an avi-tourism literacy rate of 43.66% which presupposes passive behaviour of learners towards birds, bird habitat and avi-tourism activities. Besides lacking basic bird and environmental knowledge, learners have also not yet reached the desired levels of emotional affection towards birds and the natural environment. However, increased awareness and affinity, involvement, values and behavioural intention will most likely entice pro-avi and environmental behaviour. The research poses clear challenges to professionals and educators within the tourism industry of South Africa to increase learners' willingness and motivation to act pro-environmentally through dedicated education. This supports the need to introduce an intervention programme in order to promote awareness, knowledge, values and pro-avi and environmental behaviour among learners.
Keywords: 650